Nrf2-mediated therapeutic effects of dietary flavones in different diseases - Huang, Wenkai; Zhong, Yuan; Gao, Botao; Zheng, Bowen; Liu, Yi (Frontiers in Pharmacology, 2023)
Oxidative stress (OS) is a pathological status that occurs when the body's balance between oxidants and antioxidant defense systems is broken, which can promote the development of many diseases. Nrf2, a redox-sensitive transcription encoded by NFE2L2, is the master regulator of phase II antioxidant enzymes and cytoprotective genes. In this context, Nrf2/ARE signaling can be a compelling target against OS-induced diseases. Recently, natural Nrf2/ARE regulators like dietary flavones have shown therapeutic potential in various acute and chronic diseases such as diabetes, neurodegenerative diseases, ischemia-reperfusion injury, and cancer. In this review, we aim to summarize nrf2-mediated protective effects of flavones in different conditions. Firstly, we retrospected the mechanisms of how flavones regulate the Nrf2/ARE pathway and introduced the mediator role Nrf2 plays in inflammation and apoptosis. Then we review the evidence that flavones modulated Nrf2/ARE pathway to prevent diseases in experimental models. Based on these literatures, we found that flavones could regulate Nrf2 expression by mechanisms below: (1) dissociating the binding between Nrf2 and Keap1 via PKC-mediated Nrf2 phosphorylation and P62-mediated Keap1 autophagic degradation; (2) regulating Nrf2 nuclear translocation by various kinases like AMPK, MAPKs, Fyn; (3) decreasing Nrf2 ubiquitination and degradation via activating sirt1 and PI3K/AKTmediated GSK3 inhibition; and (4) epigenetic alternation of Nrf2 such as demethylation at the promoter region and histone acetylation. In conclusion, flavones targeting Nrf2 can be promising therapeutic agents for various OS-related disorders. However, there is a lack of investigations on human subjects, and new drug delivery systems to improve flavones' treatment efficiency still need to be developed.